The effect of low-carbon pilot policy on low-carbon technological innovation in China: Reexamining the porter hypothesis using difference-in-difference-in-differences strategy - Hongwei Yu; Fei Peng; Taiping Yuan; Dandan Li; Daqian Shi (Journal of Innovation & Knowledge (JIK), 2023)
The Porter hypothesis predicts that the win-win goals of environmental improvement and economic performance can be achieved though technological innovation, but it remains to be tested in elaborated ways. Explicitly identifying the role of environmental regulation and finely clarifying the scope of technological innovation have become two important prerequisites for accurately testing the 'Porter hypothesis'. Taking China's Low-carbon Pilot Policy as a quasi-natural experiment, this paper constructs a difference-in-difference-in-differences (DDD) strategy to identify the environmental regulation, and selects the low-carbon technological innovation which may be more dependent on Low-carbon Pilot Policy as the explanatory variable, to reexamine the 'Porter hypothesis' in China. Based on the data of listed companies in China from 2007 to 2016, this paper conducts substantial empirical studies on effect estimation, robustness test and heterogeneity analysis. The results show that the Low-carbon Pilot Policy significantly promotes the low-carbon technological innovation of enterprises in high-carbon emission industries in pilot cities. The robustness test also verifies the reliability of those results which confirms the validity of 'Porter hypothesis'. However, the heterogeneity analysis finds that the testing results of 'Porter hypothesis' may vary depending on firms' characteristics. The Low-carbon Pilot Policy has a positive and significant effect on the enterprises in eastern regions or in the cities with higher R&D investment, it can also promote non-state-owned enterprises' innovation significantly. This paper may contribute to understand more about 'Porter hypothesis' in China and offer strategies for more accurately testing on 'Potter hypothesis'.
Keywords: O33; Q48; 650; DDD; Low-carbon pilot policy; Low-carbon technology innovation; Porter hypothesis